The detection of BANA micro-organisms in adult periodontitis before and after scaling and root planing by BANA-Enzymatic TM test kit: An in vivo study - Nipun Dhalla; Sudhir Patil; Krishna Kumar Chaubey; Inderpreet Singh Narula (Wolters Kluwer Medknow Publications, 2015)
Background: Many paraclinical methods are available today for an accurate assessment of the periodontal status prior and during the periodontal treatment. The microbial-enzymatic N-benzoyl-DL-arginine-2-napthylamide (BANA) test is one of the modern alternatives to bacterial cultures. It detects the presence of three periodontal pathogens in the subgingival plaque (Porphyromonas gingivalis, Treponema denticola and Tannerella forsythia). Aims and Objective: The aim and objective of this study was to detect the presence of BANA micro-organisms and also to determine the effect of scaling and root planning in adult periodontitis patients. Materials and Methods: A total number of 20 patients (80 sites) all having periodontitis were selected. Four test sites (permanent molar from each quadrant) were selected from each patient and assessed for plaque index, bleeding index and pocket depth before and after scaling and root planning. BANA test was used for the detection and prevalence of the "red complex" bacteria in plaque samples. Results: Showed that the BANA tests are statistically correlated with the severity of periodontal destruction. There was a significant correlation between the BANA test results and the quantity of bacterial plaque, the test being influenced by the composition of bacterial plaque. Conclusion: This study encourages the use of such chair-side tests for a proper diagnosis of periodontal disease and for a good evaluation of the treatment results.